PENGARUH URAIAN JABATAN, SPESIFIKASI JABATAN DAN KOMPETENSI TERHADAP KINERJA PEGAWAI NEGERI SIPIL MELALUI PENEMPATAN KERJA SEBAGAI VARIABEL MEDIASI PADA SEKRETARIAT DAERAH KABUPATEN KUPANG - Ana Risky Yulianti Selan; Simon Sia Niha; Agapitus H. Kaluge; Thomas Ola Langoday; Stanis Man (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract Performance is the result of work that is reflected in the abilities and skills of employees in completing the tasks and responsibilities assigned. Based on the performance achievements of the employees of the Regional Secretariat of Kupang Regency over the past two years, there are several performance indicators that have not been maximized because they did not reach the target and are suspected to have been influenced by job descriptions, job specifications, competencies and work placements. This study aims to determine: 1) Respondents' perceptions of job descriptions, job specifications, competence, job placement and performance of civil servants at the Regional Secretariat of Kupang Regency; 2) Significance of the influence of job descriptions, job specifications and competencies on civil servant performance; 3) Significance of the influence of job descriptions, job specifications and competencies on job placement; 4) Significance of the effect of work placement on the performance of civil servants; 5) The ability of work placements to mediate the influence of job descriptions, job specifications and competencies on the performance of civil servants. Descriptive statistical analysis shows that the variable job description, job specification, competence, job placement and performance of civil servants are in the good category. Job descriptions and respective competencies have no significant effect on the performance of civil servants and work placements. Job specifications have a significant effect on the performance of civil servants and work placements. Work placement is not able to mediate the influence of job descriptions and competencies on the performance of civil servants. Work placement is able to mediate the influence of job specifications on civil servant performance. Keywords : Job Description, Job Specifications, Competence, Work Placement, Civil Servant Performance